Mobile E-commerce website for technology-based buying selling services - Asih E.S.; Kasmi; Nguyen P.T.; Lydia E.L.; Shankar K.; Hashim W.; Maseleno A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
Buying and selling mobile phones which located at Raya Kedondong Street Waylima Subdistrict, Pesawaran District is a store that is engaged to develop, improving, and promoting the store so that it can be known outside the region. So with this, it is necessary to give easy service to the customers who are far from reach. It can be realized by (E-Commerce). Then an application system was built to help the service information about buying and selling mobile phones which uses the SDLC method, that will produce an information system related to buying and selling mobile phones. With this application, it will help the seller in managing data of ordering goods, customer data, and facilitate consumers in finding information about prices and brands of mobile phones. BEIESP.